Los escenarios históricos en el Museo y Parque Arqueológico Cueva Pintada: de la investigación a la recreación virtual - José Ignacio Sáenz Sagasti; Carmen Gloria Rodríguez Santana (Virtual Archaeology Review)
The Museum-Archaeological Park Cueva Pintada (Galdar, Gran Canaria) has promoted the implementation of virtual possibilities to improve the understanding of this site by the visiting public. The implementation of these new technologies has been based on solid historical and archaeological research, as well as a deep respect for the original archaeological remains.